Development of a national care pathway for children with anaphylaxis. (29th September 2015) - Clark, A; Warner, J; Lloydhope, K; Alfaham, M; East, M; Ewan, P; Jewkes, F; King, R; Leech, S; Maconochie, I; Sheikh, A; Sohi, D; et al.
Abstract : Aims: The Royal College of Paediatrics and Child Health has been commissioned by the Department of Health to develop national care pathways for children with allergies. The aim of the current project was to develop a national care pathway for children with anaphylaxis. The pathway focuses on standardising the level of care received by children with allergic conditions and defining the competences required to provide a high-quality service. Method: The pathway was developed by the consensus of a multidisciplinary working group based on a systematic review of evidence from the Cochrane Library, Medline, the National Guidelines Clearing House, the Scottish Intercollegiate Network and the National Institute for Clinical Excellence. The pathway was then reviewed by a broad group of stakeholders including the public. Results: The results are presented in three sections: a pathway algorithm, the competences required to deliver the pathway and evidence-based recommendations. The principal points of pathway entry are defined and the ideal pathway of care is described in discrete stages from self-care through to follow-up. For each stage of the pathway, competences in the three main categories were identified: ▸ the things a health professional should know ▸ the specific skills expected of a health professional ▸ the services or facilities to which the health professional should have access. The review of the evidence in relation to children with anaphylaxis identified four key evidence-based recommendations. Conclusion: The authors have produced a national care pathway for anaphylaxis based on an evidence review, expert consensus and stakeholder input. The authors recommend that this pathway is implemented locally by multidisciplinary care teams with a focus on creating networks between primary, secondary and tertiary care to improve services for children with allergic conditions. The intention is that the use of this tool together with audit to ensure continuous improvement in the national delivery of services for children with anaphylaxis.